ANALISIS PENJALARAN API PUNTUNG ROKOK TERHADAP LAHAN GAMBUT - Ray Kentkhute; Rukmini A.R.; Aswin Usup (Institut Teknologi Yogyakarta, 2022)
The argument that arises and is also often mentioned is that one of the sources of fire is cigarette butts that are disposed of carelessly. Cigarette butts from smokers like this are often thrown away when they are still lit and thrown carelessly into the environment they are crossing. The length of time for a cigarette flame to stay burning even though it is not smoked is what will give it the opportunity to ignite other materials that come into contact with it. The treatments in this study were 2 types of white cigarettes, 2 types of filtered kretek cigarettes, 2 types of unfiltered kretek cigarettes which were tested in contact with weed litter, shrubs and peat soil as well as hvs paper, newspaper, and tissue as comparison materials. Based on the results of analysis of variance (ANOVA) showed that each treatment of cigarette butt fire had no significant effect in each treatment. Cigarette butts that are still lit cannot ignite the fire directly on peatlands but the spread of fire from cigarette butts can occur only through the process to vegetation that lives on peatlands, especially shrubs (which are air-dried). Cigarettes that can spread their fire to the bushes with sufficient wind conditions are LA, Gudang Garam Merah, and Dji Sam Soe. The faster the average wind speed received by the cigarette butt fire, the faster it spreads.